포도 ‘Tano Red’ ×‘Ruby Seedless’ 집단에서 SNP 분자표지를 이용한 유전자지도 작성 - 정승현(Seung Hyeon Joung), 임동준(Dongjun Im), 허윤영(Youn Young Hur), 이준대(Jundae Lee) (Korean journal of breeding, 2022)
Grape (Vitis vinifera L.) is a perennial fruit tree with high heterozygosity, consisting of 38 chromosomes (2n=38), and it takes along time for grape seedlings to grow into fruit-bearing trees. Therefore, it is difficult to study grape genetics and breeding strategies. However,it has recently become possible to discover many SNPs through whole genome resequencing or genotyping-by-sequencing (GBS) analysis. In this study, we aimed to develop high-resolution melting (HRM) markers from the detected SNPs and construct a genetic linkage mapusing HRM markers. In a previous study, 2,553 SNPs were identified using GBS analysis. In this study, 1,336 SNPs were used to designprimer sets for HRM analysis. The developed HRM markers were used for construction of a genetic linkage map in an F1 segregating populationconsisting of 192 individuals from a cross between ‘Tano Red’ (V. labrusca × V. vinifera) and ‘Ruby Seedless’ (V. vinifera). A total of 805polymorphic HRM markers were developed, of which 363 were mapped onto the genetic linkage map of grape, with a total length of 1,453.5cM consisting of 19 chromosomes. This SNP-based genetic linkage map and HRM markers can be used for QTL identification and markerdevelopment for important fruit traits of grape. KCI Citation Count: 0